Pałac Działyńskich. ``Wydatki ochmistrzyni od lutego 1868 r. do 1 września 1869 r.'' (1868)
Zestawienie wydatków.
st. zas.
Keywords: Poznań; Pałac Działyńskich; Kórnik; majętność kórnicka; Majętność Kórnicka. II |Akta administracyjno-gospodarcze